تسوية منازعات الضمان االجتماعي في التشريع الجزائري - شناف مسعودة - – زيان منى (جامعة المسيلة, 2024)
هدفت الدراسة الى: - دراسة القوانين والتشريعات المتعلقة بالضمان االجتماعي في الجزائر. - فهم اآلليات واإلجراءات القانونية المتبعة في تسوية منازعات الضمان االجتماعي. - تحديد النقاط التي تحتاج إلى تحسين أو تعديل في التشريعات الحالية. من خالل دراسة الموضوع تم الخروج بمجموعة من النتائج تمثلت في: - تبين أن التشريعات الج ازئرية المتعلقة بالضمان االجتماعي، مثل القانون رقم 11-83 والقانون رقم ،12-83 توفر إطارا قانونيا شامال لحماية حقوق المستفيدين. - نظام الضمان االجتماعي الج ازئري يضمن حماية شاملة للفئات الهشة، ويوفر آليات قانونية لتسوية المنازعات بسرعة وفعالية. - وجود لجان المصالحة والتسوية الودية يعزز من حل الن ازعات بطرق توافقية قبل اللجوء إلى القضاء. الكلمات المفتاحية: الضمان االجتماعي، المنازعات، التشريع الجزائري. Abstract: The study aimed to: - Examine the laws and regulations related to social security in Algeria. - Understand the legal mechanisms and procedures followed in the settlement of social security disputes. - Identify the points that need improvement or amendment in the current legislation. Through the study of the subject, a set of findings were reached: - It was found that Algerian legislation related to social security, such as Law No. 83-11 and Law No. 83-12, provides a comprehensive legal framework for protecting the rights of beneficiaries. - The Algerian social security system ensures comprehensive protection for vulnerable groups and provides legal mechanisms for the swift and effective settlement of disputes. - The existence of reconciliation and amicable settlement committees enhances the resolution of disputes through consensual methods before resorting to the judiciary. Keywords: social security, disputes, Algerian legislation.
Keywords: الكلمات المفتاحية: الضمان االجتماعي، المنازعات، التشريع الجزائري.